Special Economic Zones in India: The Continuity Context - Singh, Ranjit; Barman, Arup (Gyan Management Journal, 2010)
A Special Economic Zone (SEZ) is a geographical region that has economic laws that are more liberc than a country’s typical economic laws. With a view to overcome the shortcomings experienced o· account of the multiplicity of controls and clearances; absence of world-class infrastructure, and a· unstable fiscal regime and with a view to attract larger foreign investments in India, the Government c. _. India announced the Special Economic Zones (SEZs) Policy. The whole idea behind the setting up of SE:. was to increase the exports and hence accelerate the economic development of the country. This poli(. intended to make SEZs an engine for economic growth supported by quality infrastructur, complemented by an attractive fiscal package. This paper gives a birds eye view about the SEi objectives and rules ofSEZ, incentives available in SEZs, benefits from SEZ, impact ofSEZ in India, ti:: arguments against the SEZ, the politics behind SEZ and finally the paper ended up wir" recommendations for the sustainability of the SEZs in the interest of the farmers and industries bot